Prospective study of ABO blood type and the risk of pulmonary embolism in two large cohort studies - Wolpin, Brian M.; Kabrhel, Christopher; Varraso, Raphaëlle; Kraft, Peter; Rimm, Eric B.; Goldhaber, Samuel Z.; Camargo, Carlos A., Jr; Fuchs, Charles S. (Thrombosis and Haemostasis, 2010)
Prior studies have suggested an association of ABO blood type and the risk of venous thromboembolism; however, most studies were retrospective and lacked important covariates or validated endpoints. Moreover, risk estimates varied widely across studies. Therefore, we prospectively examined the association of blood type and the risk of incident pulmonary embolism (PE) in two large cohort studies, the Nurses’ Health Study and Health Professionals Follow-up Study. During 1,010,378 person-years of follow-up among 77,025 women and 30,105 men, 499 participants developed PE. Compared to those with O-blood type, participants with non-O blood type had multivariable-adjusted hazard ratios (HR) of 1.86 (95% CI, 1.35–2.57) for idiopathic PE, 1.29 (95% CI, 1.03–1.62) for non-idiopathic PE, and 1.46 (95% CI, 1.22–1.76) for any PE. Hazard ratios were similar for participants with blood types A, B, and AB. Age-adjusted absolute rates of idiopathic PE over 10 years of follow-up differed by blood type: 0.11% for O, 0.20% for A, 0.19% for AB, and 0.21% for B. For idiopathic PE, the population attributable fraction was 33% for inheritance of non-O blood type. Among past and current smokers, participants with non-O vs. O-blood type had a HR for idiopathic PE of 2.56 (95% CI, 1.61–4.08). Among never smokers, the HR for idiopathic PE was 1.30 (95% CI, 0.82–2.05; Pinteraction=0.04). In two large, prospective cohorts, ABO blood type was significantly associated with the risk of idiopathic and non-idiopathic PE, with even greater risk for idiopathic PE among current and past smokers with non-O blood type.
Keywords: Pulmonary embolism; inherited coagulation disorders; epidemiological studies